Grades, aspirations and post-secondary education outcomes - Louis N. Christofides; Michael Hoy; Joniada Milla; Thanasis Stengos (Institute for the Study of Labor (IZA), 2012)
We explore the forces that shape the development of aspirations and the achievement of grades during high school and the role that these aspirations, grades, and other variables play in educational outcomes such as going to university and graduating. We find that parental expectations and peer effects have a significant impact on educational outcomes through grades, aspirations, and their interconnectedness, an issue explained in the context of a rich, longitudinal data set. Apart from this indirect path, parents and peers also influence educational outcomes directly. Policy measures that operate on parental influences may modify educational outcomes in desired directions.
Keywords: I20; J00; 330; university attendance; aspirations; peers; parents; Canada; Bildungsabschluss; Studierende; Hochschule; Motivation; Soziale Gruppe; Eltern; Kanada